DETEMINAN AUDIT DELAY PADA PERUSAHAAN GO PUBLIC SEKTOR MANUFAKTUR TERDAFTAR DI BEI - Irfan Irfan; Maya Sari; Aulia Rahman Harahap (JURNAL MUTIARA AKUNTANSI, 2020)
This research to identify the effect of audit committee size and profitability on audit delay. The population in this research all of manufacturing sector companies listed on the IDX during the 2013-2017 period. The sample of this research was selected using the purposive sampling method. Data in this study were analyzed using logistic regression analysis using SPSS. The results of this study indicate that the size of the audit committee and PROFITABILITAS both partially and simultaneously affect audit delay